Dislipidemias como factores de riesgo cardiovascular en adultos de Latinoamérica: Revisión sistemática - Agila Cuenca, Tanya Yulisa (2023)
Dyslipidemia is a group of diseases without obvious symptoms caused by metabolic dysfunction due to an increase in lipoproteins in the blood, thus causing a series of changes. To confirm this pathology quantification of the lipid profile must be performed, which has as parameters: Cholesterol, triglycerides, LDL, and HDL. This research aims to analyze the prevalence of dyslipidemia and its association with the appearance of cardiovascular diseases in adults in Latin America. The type of study is a systematic review with a scientific search strategy with publications from 2013-2023, in which 17 scientific articles were chosen. Bibliographic reviews of scientific articles in English, Spanish, and Portuguese from journals indexed in Pubmed, Scielo, Redalyc, Google Academic, and Lilacs were carried out. Among the results, it is evident that there is a high prevalence of dyslipidemias in Latin America and that the most common type is low-HDL. In conclusion, this study found different types of dyslipidemia present in adults like hypercholesterolemia, hypertriglyceridemia, low HDL, high LDL-C, mixed hyperlipidemia, secondary dyslipidemia, and atherogenic dyslipidemia, the most frequent being low HDL-c. On the other hand, the association between dyslipidemia and cardiovascular diseases was confirmed because dyslipidemia is considered one of the main risk factors that causes this type of pathology. Likewise, we must take into account that there are other risk factors like obesity, sedentary lifestyle, alcohol, accumulation of abdominal fat, among others, that contribute to the development of these cardiovascular diseases